The first skull of Anthropornis grandis (Aves, Sphenisciformes) associated with postcranial elements - Acosta Hospitaleche, Carolina Ileana Alicia (2019)
Associated penguin remains found in Bartonian levels of the Submeseta Formation (Seymour Island, Antarctica), including cranium and mandible, both partial tarsometatarsi, and some other fragmentary bones, are analyzed here. This specimen preserves the first cranium reliably assigned to the giant form Anthropornis grandis, and constitutes the first opportunity to taxonomically assign a cranial material to any of the Antarctic penguin species. A discussion of the diet preferences and feeding mechanisms of A. grandis is supported here by three-dimensional paleoneurological and cranial-jaw muscular reconstructions. We propose that A. grandis was a penguin with a voluminous musculature strongly attached to the neck and skull, adapted to chase and hunt fish during diving.